Kembar Mayang Dalam Tradisi Pernikahan Adat Jawa Masyarakat Dusun Krajan Desa Pesanggaran Kabupaten Banyuwangi (Kajian Bentuk, Fungsi Dan Makna) - Amelia Purwandini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The implementation of a ceremony in various regions throughout Indonesia must use the means that complement it, the means used in a ceremony must be different in one region from another, one example of a wedding ceremony in Java that uses twin mayang means, but these facilities are not well understood by the community, especially the younger generation today. The research entitled